2018
DOI: 10.1039/c8cc03838d
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable switching between nonporous and porous phases of a square lattice (sql) topology coordination network

Abstract: A nonporous square lattice (sql) coordination network [Co(bipy)2(NCS)2]n (sql-1-Co-NCS) exhibits recyclable switching induced by CO2. The sorption isotherms are stepped with moderate hysteresis, temperature controlled and saturation uptake is fixed. Such switching, which has rarely been observed, offers the promise of exceptional working capacity for gas storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 41 publications
1
72
0
Order By: Relevance
“…The adsorption properties of sql coordination networks remain underexplored with the notable exception of the so‐called ELM family, which exhibits single or multi‐step gas adsorption isotherms triggered by appropriate stimuli . Recently, we reported that the related compound sql‐1‐Co‐NCS exhibits recyclable switching with single‐step adsorption isotherms induced by CO 2 . These switchable sql coordination networks, which we termed switching adsorbent layered materials, have not yet been studied with respect to their sorption properties on hydrocarbon vapors and liquids, although several nonporous organic solids showed promising selectivity signatures .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The adsorption properties of sql coordination networks remain underexplored with the notable exception of the so‐called ELM family, which exhibits single or multi‐step gas adsorption isotherms triggered by appropriate stimuli . Recently, we reported that the related compound sql‐1‐Co‐NCS exhibits recyclable switching with single‐step adsorption isotherms induced by CO 2 . These switchable sql coordination networks, which we termed switching adsorbent layered materials, have not yet been studied with respect to their sorption properties on hydrocarbon vapors and liquids, although several nonporous organic solids showed promising selectivity signatures .…”
Section: Figurementioning
confidence: 99%
“…The nonporous (closed) phase [Co(bipy) 2 (NCS) 2 ] n ( sql‐1‐Co‐NCS ) was prepared using the method described recently . Single crystals of the open phases of sql‐1‐Co‐NCS were prepared via solvent diffusion: sql‐1‐Co‐NCS⋅4PX , sql‐1‐Co‐NCS⋅4MX , sql‐1‐Co‐NCS⋅4OX and sql‐1‐Co‐NCS⋅2EB (PX= para ‐xylene, MX= meta ‐xylene, OX= ortho ‐xylene, EB=ethylbenzene; full synthesis procedures are given in Supporting Information).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…At 195 K, sql-1-Co-NCS was reported to exhibit a switching or Type F-IV 21 CO 2 sorption isotherm at low pressure. 49 sql-1,3-Co-NCS, was also observed to exhibit a stepped isotherm (Fig. 3a and S22 †) with low CO 2 uptake until ca.…”
Section: Co 2 Induced Switching Behaviourmentioning
confidence: 92%
“…Herein, we describe an ew approach to C 8 aromatics separation that, counterintuitively,involves the use of anonporous material, [17] {[Co(4,4'-bipyridine) 2 (NCS) 2 ]} n (sql-1-Co-NCS), which switches to open phases when exposed to certain guests ( Figure 1). sql-1-Co-NCS belongs to abroad family of MOMs comprised of octahedral metal ions, M,c oordinated counter anions, A,a nd linear linker ligands, L.W hen M:L is 1:2then square lattice (sql)coordination networks of formula {[M(L) 2 (A) 2 ]·xguest} n are readily formed.…”
mentioning
confidence: 99%